Analisys of Village Apparaturs Performance in Implementing VIillage Goverment in Pallimae Village, Poleang District, Bombana Regency - Musnida; Achmad Lamo Said; Yudi Agusman (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Fundamental problems, such as the lack of clear Standard Operating Procedures, often confuse the community in managing administration. Furthermore, the discipline of village officials remains low, evident in their lack of punctual attendance at the office even though residents have arrived since morning. This has led to dissatisfaction and criticism from the community. The purpose of this study was to analyze the performance of Pallimae Village officials, Poleang District, Bombana Regency, in administering village governance. This study used a descriptive qualitative approach with data collection techniques through in-depth interviews, direct observation, and documentation. Data analysis techniques included examining the data, then classifying it based on the type or relevant needs, followed by verification, and finally drawing conclusions. The results showed that the performance of village officials was not fully optimal. In terms of quality indicators, the lack of written service standards resulted in inconsistent administrative processes and still contained errors. In terms of quantity, the high workload was not balanced with the limited number of human resources, resulting in service queues. The punctuality indicator was the weakest aspect due to inconsistencies in working hours and low discipline. Meanwhile, aspects of effectiveness, independence, and work commitment were deemed quite good, but were still hampered by limited infrastructure and incentives. Other major obstacles included a lack of public understanding of administrative requirements and slow disbursement of incentives for civil servants.